Desajustes democráticos y retóricas del silencio. - SALOMÓN GEBHARD, JOSÉ (Nomadías)
The article analyzes the process that led to the defeat of the option for a new constitution in the Chilean plebiscite. It highlights the return to silence and censorship for those who seek to place the marginal in the center. The prevalence of a spectacle culture that seeks visibility and discursive homogenization is mentioned. However, the emergence of new subjectivities that confront consensual rhetoric and produce representation mismatches is also highlighted. The importance of seeking spaces for rehistoricization and recreation of subjects from the local perspective, especially from a gender perspective, is emphasized.